Tumor Infiltrating Lymphocytes and Macrophages Improve Survival in Microsatellite Unstable Colorectal Cancer - Narayanan, Sumana (Sci Rep, 2019)
Due to the loss of DNA repair mechanisms in colorectal cancer (CRC) with microsatellite instability (MSI), somatic mutations accumulate within DNA; making them more prone to attack by tumor infiltrating lymphocytes (TIL) and macrophages. We hypothesize that MSI-High (MSI-H) patients have favorable survival due to increased tumor immunogenicity. The Cancer Genome Atlas (TCGA) was used to evaluate gene expression from 283 patients with CRC, comparing MSI-H and microsatellite stable (MSS) patients. CIBERSORT algorithm estimated the fraction of immune cell types. We found that low expression of DNA repair genes (MLH1, MLH3, PMS1, PMS2, ATR, PRKDC, ATM, BRCA2) associated with MSI-H. MSI-H was directly associated with Helper T-cells (p = 0.034) and M1 macrophages (p < 0.0001). MSI-H tumors associated with diminished intra-tumoral heterogeneity as well as higher expression of checkpoint molecules PD-1, PD-L1, CTLA4, LAG3 and TIM3 (p < 0.0001). Improved OS was seen in patients with low ATM, PMS2 and MLH3. In the TCGA CRC cohort, decreased expression of DNA repair genes associated with MSI-H. MSI-H patients had improved survival, likely due to higher TIL and M1 macrophage infiltration as well as lower intra-tumoral heterogeneity. MSI-H also associates with expression of immune checkpoint molecules with potential for development of therapeutic targets.